(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of the article is the energy potential analysis of willow cultivated for ener-gy purposes on marginal lands (V, VI quality classes). The energy potential analysis was prepared for every voivodeship in Poland. The first part of the article presents the current cultivation acreage of willow used for energy purposes in Poland.The second part rates the energy potential of cultivating willow on the marginal lands. The highest theoretical energy potential characterizes wielkopolskie, mazowieckie, łódzkie and podlaskie voivodeships, while opolskie, śląskie and lubelskie voivodeships have the lowest energy potential.It has been estimated that the total theoretical energy potentialthat could be obtained from cultivating willow can reach the level of 99,4 thousand TJ annually.This estimated potential could meet about 20% of the country’s energy needs.